Study on the behaviour of the concrete sleeper / Mohamad Kamal Idris - Idris, Mohamad Kamal (Faculty of Civil Engineering, 1993)
This experimental project consists of preparing, fabricating and testing of prestressing post-tensioning concrete sleeper. The test specimen is tested simply supported and two point loads placed on the location of rail seats. The load applied until the prestressed post-lensioned concrete sleeper fails. In this study only two samples of concrete sleeper is prepared and tested. The experimental results will be compared to the finite element programe "ANALYSIS SYSTEM” (ANSYS). The test specimen load-deflection relationship, load-strain relationship will be produced, and the location of cracking will be shown.